2011
DOI: 10.1063/1.3572264
|View full text |Cite
|
Sign up to set email alerts
|

A self-consistent global model of solenoidal-type inductively coupled plasma discharges including the effects of radio-frequency bias power

Abstract: We developed a self-consistent global simulator of solenoidal-type inductively coupled plasma discharges and observed the effect of the radio-frequency (rf) bias power on the plasma density and the electron temperature. We numerically solved a set of spatially averaged fluid equations for charged particles, neutrals, and radicals. Absorbed power by electrons is determined by using an analytic electron heating model including the anomalous skin effect. To analyze the effects of rf bias power on the plasma prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 28 publications
(53 reference statements)
0
17
0
Order By: Relevance
“…The electron heating module uses a spatially averaged electron temperature equation [11]. The equation can be arranged as in Eq.…”
Section: Plasma Modulementioning
confidence: 99%
See 2 more Smart Citations
“…The electron heating module uses a spatially averaged electron temperature equation [11]. The equation can be arranged as in Eq.…”
Section: Plasma Modulementioning
confidence: 99%
“…We estimate that this tendency related with electron density around particle. From researches of Kwon et al [11,12] and Bae et al [13], we could predict that electron density increase as induced plasma source power increase. And this effect could increase the repulsive force between charged particles.…”
Section: Plasma Source Powermentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, some theoretical research has also been put forward to investigate the bias effect in a combined plasma reactor with both ICP power and RF bias. 8,[14][15][16][17][18][19] Rauf et al 8 employed the hybrid plasma equipment model (HPEM) with a detailed plasma chemistry description and showed that the RF bias power had very little effect on the ion and electron densities in an Ar/SF 6 discharge. Hoekstra and Kushner 14 focused on the IED by using the HPEM coupled with the plasma chemistry Monte Carlo simulation module.…”
Section: Introductionmentioning
confidence: 99%
“…Tinck et al 16 illustrated with the HPEM that the energy and fluxes of the ions hitting the substrate became higher at increasing bias, and this gave rise to a higher etch rate. Kwon et al 17 presented a self-consistent global model combined with a sheath module to examine the bias power effect on the plasma properties. Finally, Zhang and Kushner 18 and Rauf 19 investigated the influence of the bias power on the etch rate in C 2 F 6 and CF 4 /O 2 plasmas, respectively.…”
Section: Introductionmentioning
confidence: 99%